The Dramatization of the Cybersublime in Jennifer Haley’s The Nether - Diana Jawad Abdul Kathem; . Mithal Madlool Al Bederi (مجلة الباحث, 2026)
The cybersublime refers to the feeling of awe, wonder, and fear in virtual environments. Unlike the Romantic sublime, which arise from the encounter with nature, the cybersublime arise from the overwhelming experience of the vastness and possibilities offered by cyber realms. The cybersublime as a concept, which is the core of this study becomes a topic of interest to many playwrights, such as Jennifer Haley, the American contemporary playwright. Her works like The Nether (2013) deals with the ethical concerns in virtual realms and its impact on human relations. The play is about the Nether,